Pathophysiology of sinusitis of odontogenic origin. Issue 2 (14th December 2015) - Taschieri, Silvio; Torretta, Sara; Corbella, Stefano; Del Fabbro, Massimo; Francetti, Luca; Lolato, Alessandra; Capaccio, Pasquale
Abstract: Sinusitis of odontogenic origin, which is frequently encountered in routine otolaryngological and dental clinical practice, has been described as a reactive maxillary inflammation secondary to maxillary tooth infection or trauma to an odontogenic disease of maxillary bone, dental extractions, implant placement, or endodontic treatment impairing the integrity of the Schneiderian membrane. The aim of the present review was to investigate and discuss the most recent pathophysiological findings, predisposing odontogenic factors, microbiology, and the possible involvement of bacterial biofilms (BB) in the development of sinusitis. The narrative literature review showed that there might be a correlation between the bacteria present in pathological teeth in communication with the sinus and those found in infected sinus. The formation of a BB might be also involved in the etiopathogenesis of sinusitis of odontogenic origin. In conclusion, the true origin of odontogenic sinusitis is still unresolved. In clinical terms, the choice of suitable therapy depends on the characteristics of the biofilm. Further microbiological studies are required to better investigate the role of BB.